PEMODELAN KOLIMATOR DI RADIAL BEAM PORT REAKTOR KARTINI UNTUK BORON NEUTRON CAPTURE THERAPY (BNCT) - , BEMBY YULIO VALLENRY ([Yogyakarta] : Universitas Gadjah Mada, 2014)
One of the cancer therapy methods is BNCT (Boron Neutron Capture Therapy). BNCT utilizes neutron capture by 10B deposited on cancer cells. The superiority of BNCT compared to other radiation therapy is the high level of selectivity since its level is within cell. This study was carried out on collimator modeling in radial beam port of Reaktor Kartini for BNCT. The Modeling was conducted by simulation using software of Monte Carlo N-Particle version 5 (MCNP 5). MCNP 5 is a package of the programs for both simulating and calculating the problem of particle transport by following the life cycle of a neutron since its birth from fission reaction, transport on materials, until eventually lost due to the absorption reaction or out from the system. The collimator modeling used materials which varied in size in order to generate the value of each of the parameters in accordance with the recommendation of the IAEA, the epithermal neutron flux (Î¦epi) > 1.0 x 109 n.cm-2.s-1, the ratio between the neutron dose rate fast and epithermal neutron flux ( Ìf/Î¦epi) < 2.0 x 10-13 Gy.cm2.n-1, the ratio of gamma dose rate and epithermal neutron flux ( ÌÎ³/Î¦epi) < 2.0 x 10-13 Gy.cm2.n-1, the ratio between the thermal and epithermal neutron flux (Î¦th/Î¦epi) < 0.05 and the ratio between the current and flux of the epithermal neutron (J/Î¦epi) > 0.7. Based on the results of the optimization of the modeling, the materials and sizes of the collimator construction obtained were 0.75 cm Ni as collimator wall, 22 cm Al as a moderator and 4.5 cm Bi as a gamma shield. The outputs of the radiation beam generated from collimator modeling of the radial beam port were Î¦epi = 5.25 x 106 n.cm-2.s-1, Ìf/Î¦epi = 1.17 x 10-13 Gy.cm2.n-1, ÌÎ³/Î¦epi = 1.70 x 10-12 Gy.cm2.n-1, Î¦th/Î¦epi = 1.51 and J/Î¦epi = 0.731. Based on this study, the results of the beam radiation coming out of the radial beam port did not fully meet the criteria recommended by the IAEA.